Urban Development and its Future Prospects in the City of Kufa - Abdul-Katib, Dr. Wrood Mohsen (Journal of Innovation in Education and Social Research, 2025)
Urban development is a topic of great importance to both developed and developing countries, although developing countries need greater seriousness in caring about development, as the interest has increased day after day, due to its importance in all areas of life, as it is not limited to the economic and social aspects only, but rather makes the human being its starting point and goal and deals with him as the active element in it, as the goal of development is to advance society from a fixed state to a higher and better state, And what it reaches of good to exploit the energies available to it and existing and latent and employ them for the best. Development seeks to expand options and enjoy its fruits in the form of food, clothing, housing, health services, political and cultural freedoms and participation in the environment in which it lives. Accordingly, development enriches social segments at the expense of the poorest groups and disrupts the social and political balance and destroys the environment is the opposite of urban development. The research included the main development indicators represented by health and education as they are main indicators in measuring the level of human development. The research aims to know the reality of urban development in the city of Kufa, and then evaluate the level of this development through its main indicators (education, health, income), in addition to studying the basic services in the city (potable water, sewage, electricity, transportation methods, municipal services) based on planning standards. At the end of the research, the researcher reached a set of conclusions and recommendations that the researcher hopes will achieve some benefit in achieving urban development in the city of Kufa.